2014
DOI: 10.3109/07357907.2014.958231
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Stem Cell Hypothesis: A Guide to Potential Molecular Targets

Abstract: Common cancer theories hold that tumor is an uncontrolled somatic cell proliferation caused by the progressive addition of random mutations in critical genes that control cell growth. Nevertheless, various contradictions related to the mutation theory have been reported previously. These events may be elucidated by the persistence of residual tumor cells, called Cancer Stem Cells (CSCs) responsible for tumorigenesis, tumor maintenance, tumor spread, and tumor relapse. Herein, we summarize the current understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 316 publications
3
63
0
Order By: Relevance
“…Another hypothesis is that normal stem cells have similar location as CSC and a niche signal from normal stem cells induces CSC [37]. Some authors have shown that CSC phenotype can be acquired by tumor cells that have previously negative stem cell markers [35]. More recently, it has been defended a dedifferentiation of non-CSC into CSC, a similar phenomenon described in somatic cells that can be dedifferentiated to the pluripotent cells [38].…”
Section: Cancer Stem Cellsmentioning
confidence: 97%
See 3 more Smart Citations
“…Another hypothesis is that normal stem cells have similar location as CSC and a niche signal from normal stem cells induces CSC [37]. Some authors have shown that CSC phenotype can be acquired by tumor cells that have previously negative stem cell markers [35]. More recently, it has been defended a dedifferentiation of non-CSC into CSC, a similar phenomenon described in somatic cells that can be dedifferentiated to the pluripotent cells [38].…”
Section: Cancer Stem Cellsmentioning
confidence: 97%
“…This theory points the presence of a subpopulation that initiates and develops the tumor [34]. CSC are recognized as responsible for tumorigenesis, tumor differentiation, tumor maintenance, tumor spread, and tumor relapse [35]. Self-renewal capacity is regulated by several pathways, namely Wnt, Notch, and Hedgehog.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 The selection of mAb directed at surface antigens expressed by tumor cells has enabled the development of new reagents for diagnostic purposes or for targeted therapies. 15,16 Magnetic resonance imaging (MRI) is a well-recognized tool for in vivo cell tracking because of its high spatial and contrast resolution, as well as its reproducibility. Combined with an advanced contrast agent, MRI allows for molecular profiling of target tissues/cells and can enable the early detection of malignancies, making more accurate staging and treatment monitoring possible.…”
mentioning
confidence: 99%